Transparansi dan Akuntabilitas Pengelolaan Keuangan di Desa Wisata Kajii Gilangharjo, Pandak Bantul - Suswanta, Suswanta; Setiawan, Anang (Unri Conference Series: Community Engagement, 2024)
This article describes the financial management of the ornamental fish tourism village Kadisoro Nyawiji dadi siji (Dewi Kajii), Gilangharjo, Pandak, Bantul in a transparent and accountable manner. Implementation is through systematic bookkeeping, regular reporting, and external audits. The three activities are carried out to mitigate financial risks and increase stakeholder trust. The application of technology such as modern accounting software and the conduct of independent audits ensure effective financial oversight thus contributing to an efficient management process. Data collection techniques were carried out by interviews, documentation and Focus Group Discussions with community leaders and tourism village managers. The analysis technique was carried out using qualitative methods. Dewi Kajii's financial management can be a model for other tourist village managers because it has proven to be effective and contributive to the economic development of the community.